Interpreting Art - Rose, Sam (Spotlights, 2022)
How do people make sense of works of art? And how do they write to make others see the same way? There are many guides to looking at art, histories of art history and art criticism, and accounts of various 'theories' and 'methods', but this book offers something very unlike the normal search for difference and division: it examines the general and largely unspoken norms shared by interpreters of many kinds. Ranging widely, though taking writing within the Western tradition of art history as its primary focus, Interpreting Art highlights the norms, premises, and patterns that tend to guide interpretation along the way. Why, for example, is the concept of artistic 'intention' at once so reviled and yet so hard to let go of? What does it really involve when an interpretation appeals to an artwork's 'reception'? How can 'context' be used by some to keep things under control and by others to make the interpretation of art seem limitless? And how is it that artworks only seem to grow in complexity over time? Interpreting Art reveals subtle features of art writing that are central to the often unnoticed interpretative practices through which we understand works of art. In doing so, the book likewise illuminates various choices or crossroads where things could be otherwise, pointing to how historians and critics might choose to operate differently in the future.